Strategi Dakwah dalam Penebar Perdamaian - Jihan Nur Millasari; Ismiati Asfufah; Yuyun Mujidah; Sutomo (Jurnal Teologi Islam, 2025)
This study examines the concept, urgency, and strategies of dakwah (Islamic preaching) in promoting peace, particularly within Indonesia’s plural and dynamic society. In Islam, dakwah is not merely understood as the transmission of religious teachings, but also as a means of social transformation aimed at fostering harmony, preventing conflict, and strengthening the values of tolerance. This research employs a library-based approach, reviewing the Qur’an, Hadith, classical literature, works of contemporary scholars, and relevant academic journals. The findings identify five key strategies for peaceful dakwah: (1) a humanistic approach emphasizing empathy, constructive dialogue, and two-way communication; (2) consistent uswah hasanah (exemplary conduct) in daily life; (3) creative and ethical utilization of digital media to engage younger generations; (4) strengthening multicultural and interfaith dakwah as a means to foster social cohesion; and (5) community empowerment through socio-economic programs grounded in Islamic values. The implementation of these strategies requires strong communication skills, deep contextual understanding, and high moral integrity on the part of the da’i. This study affirms that strengthening peaceful dakwah based on the rahmatan lil ‘alamin principle is a strategic step toward building an inclusive, just, and civilized society in the era of globalization.